Ο ποιητής ως προφήτης και ως πιερότος στην ποίηση του Ρώμου Φιλύρα: Οι επιβιώσεις της ρομαντικής ιδεολογίας - Ζένιος, Σίμος (Σύγκριση/Comparaison/Comparison, 2018)
This article argues that Romos Philyras adopts the persona of the Pierrot in the work of Romos Philyras in order to critically appropriate the romantic topos of the poet as prophet. Whereas many symbolist and modernist poets have resource to the figure of the pierrot precisely in order to oppose and demystify high romanticist ideology, I demonstrate that Philyras conjoins the two personae —prophet and pierrot. Employing methodological insights from phenomenological approaches to lyric poetry and enriching them with emphasis on formal and prosodic features, I propose a reading of Philyras’s “Pierrot” (1922) that argues against an anthropomorphizing understanding of the relationship between lyric I and the puppet-pierrot. I highlight instead that for Philyras it is precisely the lack of self-consciousness and self-reflective discourse that is the shared ground between the two personae. Contextualizing my reading with pertinent texts from the European tradition (Heinrich von Kleist, Henri-Louis Bergson), I pursue the relationship between anti-humanism and poetic prophecy in Philyras’s prose work in order to throw in relief the forceful and violent character of the visionary experience.